A Comparison of Accuracy between IMMULITE2000® and GENEDIA® for Helicobacter pylori Infection - Seon Hee Lim; Nayoung Kim; Sung Eun Kim; Gwang Ho Baik; Ju Yup Lee; Kyung Sik Park; Jeong Eun Shin; Hyun Joo Song; Dae-Seong Myung; Suck Chei Choi; Hyun Jin Kim (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Background/Aims In serological tests for Helicobacter pylori (H. pylori), an enzyme-linked immunosorbent assay (GENEDIA®) and a solid-phase, two-step chemiluminescent enzyme immunoassay (IMMULITE®), which are easy to perform, inexpensive, and widely available, are commonly used. However, local validation of the test performance of IMMULITE® is required. This study aimed to examine the performance of IMMULITE® in comparison with that of GENEDIA® in a Korean health checkup population. Materials and Methods The sera of 300 subjects among those who underwent health checkup were analyzed using IMMULITE®, and results were compared with those of GENEDIA®. The two serological tests were compared for their ability to predict atrophic gastritis (AG) or intestinal metaplasia (IM) on endoscopy. Results We found significant correlation (Pearson correlation coefficient=0.903, P<0.0001) and an almost perfect agreement (Cohen’s Kappa coefficient=0.987, P<0.0001) between the results of GENEDIA® and IMMULITE®. The area under the receiver operating characteristics curve (AUC) for AG using GENEDIA® and IMMULITE® were 0.590 and 0.604, respectively, and showed no statistically significant difference in predictive ability for AG (Z-statistics=-0.517, P=0.605). The AUC for IM by GENEDIA® and IMMULITE® were 0.578 and 0.593, respectively, with no statistically significant difference in predictive ability for IM between the two values (Z-statistics=-0.398, P=0.691). Conclusions No statistically significant difference in diagnostic value for H. pylori infection was found between GENEDIA® and IMMULITE®.